Cuadernos audiovisuales de laboratorio: hacia una mejora en la enseñanza de la Química - Permanente de Física y Química, Equip Seminario (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The Audiovisual Laboratory Notebooks are framed into the so-called «active methods for Chemistry teaching», and try to achieve an effective learning, more accurate and at the same time more agreable of the techniques and usual operations in the laboratory, and also a positive attitude towards Chemistry.